(untitled) (Medical Forum Monthly, 2023)
Objective: To study association between low dose aspirin and serum uric acid level in middle age and elderly population of Karachi. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Medicine, Fatima Hospital, Baqai Medical University, Karachi from 15th December 2022 to 15th February 2023. Materials and Methods: A sample of 366 participants, aged more than 40 years, who had cardiovascular diseases or were at increased risk of cardiovascular disease were included in study. They were divided into two groups on basis of aspirin use:1) Those who are using low dose aspirin for more than one month 2) Those who have never used aspirin or did not take it for more than one month. After a brief physical examination, blood sample were taken for serum uric acird, lipids & blood sugar level. Data was analysed using appropriate statistical test, to observe difference in uric acid level and some other parameters in two groups on basis of aspirin useo Results: Prevalence of hyperuricemia was significantly lower in individuals using low dose aspirine for more than one month. (11.2% Vs 39.79% p = 0.003). Asprin use was also not associated with renal dysfuntion. Better renal functions were observed in aspirin users as compared to non-aspirin users. (eGFR 104.68±14.23 Vs 99.70±15.28 p = 0.001). Hyperuricemia was significantly associated with metabolic conditions like higher BMI, diabetes mellitus and hypercholesterolelmia. Conclusion: Use of low dose aspirin for primary or secondary prevention of cardiovascular diseases is not associated with hyperuricemia in middle aged and older population.